The influence of personal and multicultural wisdom on the adherence to the ethical principles of multicultural counselor’s candidates - Herdi Herdi (Universitas Negeri Padang, 2021)
The excellent performance of multicultural counselors are influenced by wisdom and counselor adherence to ethical principles. This study is to examine the influence of personal wisdom and multicultural wisdom on the adherence to the ethical principles of multicultural counselor’s candidates. This study used a correlational method with 517 counselor’s candidates from 11 Guidance and Counseling Departments in Indonesian. The research data was collected by using Three-Dimensional Wisdom Scale-Short Form, the Wisdom Scale for Multicultural Counselors, and the Counselor’s Principles of Ethical Scale. The data analysis technique used correlation and multiple linear regressions. The results show that there was a significant positive effect between personal wisdom and multicultural wisdom on adherence to the ethical principles of multicultural counselor’s candidates. The implication is that counselor educators need to facilitate the development of personal wisdom and multicultural wisdom to increase adherence to the ethical principles in counseling education and supervision.